Engineering of Germanium Tunnel Junctions for Optical Applications - Koerner, Roman; Fischer, Inga Anita; Schwarz, Daniel; Clausen, Caterina Johanna; Hoppe, Niklas; Schulze, Jörg (Ieee Photonics Journal, 2018)
Data transfer across millimeter-scale electrical wires is limited by both data rates and power density, which creates a performance bottleneck for semiconductor microchips in modern computer systems. Hence, silicon based platforms for optical communication are diligently explored for an on-chip optical data transfer. Semiconductor optical amplifiers provide signal recovery and loss compensation in advanced photonic circuits and are, thus, indispensable components for such platforms. However, silicon photonic components have to operate at much lower voltages and energy-per-bit metrics before it is worth integrating them on-chip with a CPU. The usage of tunnel junctions to control carrier injection can provide a fast and energy-saving alternative. Here, we present experimental results on direct conduction band carrier modulation in the indirect semiconductor Ge by Zener tunnel injection. Electrons are injected by a reverse-biased p-n Zener tunnel diode and recombine radiatively with holes injected by a forward biased p-i-n diode. This injection mechanism favors tunneling of electrons into the direct conduction band valley with concomitant improvements of optoelectronic properties. Benchmarking the performance, 2.42 dB transmission change at 0.9 V bias (1660 nm) at 300 K confirm the working principle. Our device can serve as a starting point to investigate the benefits of tunnel injection for silicon photonic devices.
CRIS-Team Scopus Importer:2021-06-29
Keywords: germanium; integrated optical devices; silicon photonics; tunnel injection; Zener tunneling; Zener-emitter